Information Hygiene: A Challenge and an Opportunity for Libraries and Librarians - Dombrovská, Michaela (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2026)
This paper explores information hygiene as a crucial framework for fostering a healthy digital lifestyle and promoting overall resilience. It traces the concept's evolution, noting its increasing relevance amid rising challenges like artificial intelligence, misinformation, disinformation, and digital addiction, exacerbated by recent global events. The study integrates findings from two comparative research projects on student information behavior in Czechia and Slovakia, alongside an analysis of Czech national reports on digital addictions. These investigations consistently reveal student concerns regarding digital distress and the negative impact of technology on personal interactions. The paper proposes information hygiene as a comprehensive approach, resting on information literacy, cybersecurity, and digital resilience. It emphasizes that effective information hygiene involves both sound information habits and healthy lifestyle habits that bolster overall well-being. A case study of a new university course on information hygiene demonstrates its practical application. Ultimately, public libraries are identified as key institutions uniquely positioned to champion information hygiene, empowering individuals to navigate the complex digital world with greater resilience.